2016
DOI: 10.1074/mcp.m115.050401
|View full text |Cite
|
Sign up to set email alerts
|

Translating Proteomic Into Functional Data: An High Mobility Group A1 (HMGA1) Proteomic Signature Has Prognostic Value in Breast Cancer

Abstract: Cancer is a very heterogeneous disease, and biological variability adds a further level of complexity, thus limiting the ability to identify new genes involved in cancer development. Oncogenes whose expression levels control cell aggressiveness are very useful for developing cellular models that permit differential expression screenings in isogenic contexts. HMGA1 protein has this unique property because it is a master regulator in breast cancer cells that control the transition from a nontumorigenic epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…important booster of the transformation process 41 , even though a perfect correlation of gene expression at mRNA and protein levels is not always observed 42 . However, data described in the previous section provided interesting evidences suggesting that the integration of proteomic and transcriptomic data, correlated by common biological functions, may highlight the potential involvement of subsets of genes in neoplastic transformation.…”
Section: Correlation Between Ape1 and Its Protein-binding Partners Atmentioning
confidence: 99%
“…important booster of the transformation process 41 , even though a perfect correlation of gene expression at mRNA and protein levels is not always observed 42 . However, data described in the previous section provided interesting evidences suggesting that the integration of proteomic and transcriptomic data, correlated by common biological functions, may highlight the potential involvement of subsets of genes in neoplastic transformation.…”
Section: Correlation Between Ape1 and Its Protein-binding Partners Atmentioning
confidence: 99%
“…A label-free shotgun proteomic approach revealed a signature of 21 proteins in a High Mobility Group A1 (HMG1) silenced TNBC cell line which was associated with poor prognosis 103 . A unique HMG1-linked sub protein signature of three proteins - kinesin family member C1(KIFC1); thyroid hormone receptor interacting protein 13 (TRIP13); and leucine-rich repeat containing 59 (LRRC59) - was unexplored in TNBCs.…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…A unique HMG1-linked sub protein signature of three proteins - kinesin family member C1(KIFC1); thyroid hormone receptor interacting protein 13 (TRIP13); and leucine-rich repeat containing 59 (LRRC59) - was unexplored in TNBCs. KIFC1, TRIP13, and LRRC59 proteins are downstream targets of HMG1 and involved in cell motility 103 . Another label-based proteomics study reported that PTPN12, a tyrosine phosphatase, inhibited cellular transformation and metastasis of TNBC cells 104 .…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…High mobility group protein HMG-I/HMG-Y (HMGA1) abundance level was found to be associated with breast cancer clinicopathological features. Maurizio et al utilized label-free shotgun MS to analyze the proteins extracted from HMGA1-silenced cells and control breast cancer cell line MDA-MB-231 176 . Ning Qing Liu et al evaluated numerous approaches for global proteome quantification and proteins involved in a signaling pathway in breast cancer tissues were identified (Figure 6 c) 177 .…”
Section: Application Of Ms In Cancer Biomarker Discoverymentioning
confidence: 99%